Analyses of magnetic properties and crystal size on Fe3O4 nanoparticle from local iron sand using PEG as soft template. (July 2020) - Mufti, N; Sari, D R P; Muyasaroh, A F; Yudyanto; Sunaryono; Taufiq, A
Abstract: Nano-sized Fe3 O4 has been considered prominent in material science research due to its potential applications in multi-layered aspects. One of the simple and inexpensive methods of nanosized Fe3 O4 synthesis is co-precipitation. However, this method has not provided a uniform size. Therefore, this study carried out a few modifications by using PEG-200 and PEG-1000 as a soft template with a volume ratio of 1:1, 1:3, and 1:5. The Fe precursors used in this study are iron sand from the Brantas River, Kediri-East Java, Indonesia. The XRD results showed that the use of PEG in the synthesis of Fe3 O4 did not affect the Fe3 O4 phase, and this study obtained a crystal size with a range of 6-12 nm. Based on morphological observations using SEM, the use of soft templates in Fe3 O4 synthesis can reduce agglomeration rather than without using a PEG template. All Fe3 O4 powder samples showed ferrimagnetic behavior with a saturation magnetization of 39.5-70 emu/g.